Physico-Chemical Characteristics of Underground water Quality of Some Villages of Jhunjhunu District of Rajasthan, India - Babita Kumari; Gupta Y.K. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Physico-chemical characteristics of underground water of Some Villages of Jhunjhunu District of Rajasthan, India have been studied. Water samples of the 15 villages from Jhunjhunu District of Rajasthan were collected and analysed for physico-chemical parameters like electrical conductivity, pH, temperature, total hardness, total dissolved solids, and concentrations of ions like sodium, potassium, fluoride, chloride, nitrate and sulphate. The result were compared with the drinking water standards of WHO (1973) and ISI (10500-91). The study indicates the need for monitoring of underground water for physico-chemical characteristics in study area. An efficient calculations were made to calculate the correlation coefficient ‘r’ along with the parameters and the study give an idea about the positive and significant correlation of TH with TDS, SO4-2 and Cl- ion concentrations, while TH show outstanding correlation with Cl- ion concentrations.